Vulnerabilities Diagnosis of Teachers of a School of Nursing: The Influence of Context - Raíla Souza Santos; Danielle Copello Vaz; Davi Silveira Barroso Alves; Florence Romijn Tocantins; Mônica Alves Vianna; Thiago Luiz Nogueira Silva (Universidade Federal do Estado do Rio de Janeiro, 2010)
The study includes an account of the academic experience of undergraduate nursing, have been faced with the challenge of diagnosing the vulnerabilities of a group of teachers relating the context in which this group is inserted, and the facilities of the School of Nursing and information about lifestyle. OBJECTIVE: To report the experience of a group of scholars to identify the vulnerabilities of their own teachers education institution and propose actions to minimize them. METHODS: This is a study of an experience. RESULTS: We collected thirteen diagnosis of vulnerabilities to this group and proposed actions political-administrative and nursing in order to reverse the vulnerabilities found. CONCLUSION: The identification of vulnerabilities directly influence the planning of nursing actions that minimize, taking as a starting point for action the causes and factors that make up the teachers' health nursing.